Performance of broiler fed on diet containing deoiled Koroch (Pongamia Pinnata) seed cake treated with NaOH and HCl - Habib, Masuma; Ferdaus, Abu Jafur Md; Islam, Md Touhidul; Hassin, Begum Mansura; Ali, Md Shawkat (Research in Agriculture Livestock and Fisheries, 2016)
The study was conducted to investigate whether the productive performances and meat yield characteristics of broiler would be improved by feeding diet containing koroch (Pongamia Pinnata) seed cake (KSC) treated with NaOH and HCl. A total number of 160 day-old straight run broiler chicks were fed on 4 iso-energetic and iso-nitrogenous diets containing either basal diet with no KSC or basal diet containing 2% KSC treated with or without 1% NaOH or 1% HCl for a period of 28 days. These diets were considered as 4 different treatments. Each treatment was replicated 4 times, each having 10 birds. Inclusion of 2% KSC treated with NaOH or HCl in the diet resulted in lower live weight, live weight gain, feed intake, feed efficiency of broilers at all ages compared to inclusion of dietary 2% KSC alone (P<0.01). However, broilers, irrespective of age, fed on diet containing 2% KSC treated with 1% HCl exhibited better productive performances than those fed on 1% NaOH treated 2% KSC incorporated diet. The amount of feed intake of broilers on either KSC alone or HCl treated KSC was almost similar to that on control diet. The meat yield parameters showed a non-significant treatment effect except for the percentage of dressing yield, liver, gizzard, head and skin weight. Dressing percentage of broilers fed on HCl treated KSC at 2% level was significantly (P<0.05) lower compared to any other dietary treatment, whereas broilers in 2% KSC dietary group showed similar results to the control group. Percentage of head and skin weight relative to body weight were higher in treated (NaOH or HCl) KSC dietary group compared to either KSC alone or control group. However, the highest liver and gizzard weights were obtained from the broilers fed on diet containing 2% KSC treated with 1% HCl, followed by diet with 1% NaOH treated KSC, KSC alone diet and the control diet. The results of the present study clearly indicated that neither the 1% NaOH treated nor 1% HCl treated KSC alliviated the depressed productive performances and meat yield characteristics of broilers. It is concluded that the poor productive performances of broilers fed on KSC incorporated diet cannot be improved by treating KSC with either NaOH or HCl, and the oil extracted KSC may contain leftover oil which might have a potential toxic effect on growth and meat yield of broilers. Res. Agric., Livest. Fish.3(2): 323-329, August 2016